2015
DOI: 10.1007/s12529-015-9496-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Acceptance in a Low-Intensity, Group-Based Acceptance and Commitment Therapy (ACT) Chronic Pain Intervention

Abstract: BackgroundAcceptance and commitment therapy has shown to be effective in chronic pain rehabilitation, and acceptance has been shown to be a key process of change. The influence of treatment dose on acceptance is not clear, and in particular, the effectiveness of a non-intensive treatment (<20 h) in a tertiary pain clinic is required. PurposeThe purpose of the study was to assess the effectiveness of a low-intensity, acceptance and commitment therapy (ACT) group program for chronic pain. The study sought to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…Parent psychological flexibility has also been shown to be positively correlated with child pain acceptance and functioning and negatively correlated with child depression and parent protective behavior 19, 49 . These parent psychological dimensions can be targeted in treatment, and there has been a track record for success in patients with chronic pain 1, 3, 20–22, 40, 51 . Additional research examining these parent dimensions is needed as well as the expansion and modification of parent interventions to address these additional and salient treatment targets.…”
Section: Discussionmentioning
confidence: 99%
“…Parent psychological flexibility has also been shown to be positively correlated with child pain acceptance and functioning and negatively correlated with child depression and parent protective behavior 19, 49 . These parent psychological dimensions can be targeted in treatment, and there has been a track record for success in patients with chronic pain 1, 3, 20–22, 40, 51 . Additional research examining these parent dimensions is needed as well as the expansion and modification of parent interventions to address these additional and salient treatment targets.…”
Section: Discussionmentioning
confidence: 99%
“…[41] More and more evidence-based data have demonstrated that the role of acceptance in coping strategies for chronic pain are growing, and acceptance-based inventions are thought to be promising. [42,43] Clinicians should recognize the importance of psychological counseling and try to encourage patients to live and to pursue their own goals with less concern about feelings of pain. Meanwhile, patients themselves also need to become aware that cognitive responses, such as beliefs, thoughts, or expectations, played a key role in the perception of chronic pain and therapeutic adjustment to pain.…”
Section: Discussionmentioning
confidence: 99%
“…Each item is scored from 0 (never true) to 6 (always true). The CPAQ has been shown to be valid and reliable, with good internal consistency and sensitivity to change [ 55 ] and the shortened version has demonstrated a sound factor structure and similar psychometric properties to the CPAQ [ 56 , 57 ]. The CAQ-8 is a shortened version of the original 18-item Committed Action Questionnaire, which assesses an individual’s persistence and flexibility in acting in the direction of valued goals [ 58 ].…”
Section: Methodsmentioning
confidence: 99%